Genealogy of obedience : reading North American dog training literature, 1850s-2000s - Włodarczyk, Justyna (Human-animal studies, 2018)
In Genealogy of Obedience Justyna Włodarczyk provides a long overdue look at the history of companion dog training methods in North America since the mid-nineteenth century, when the market of popular training handbooks emerged. Wlodarczyk argues that changes in the functions and goals of dog training are entangled in bigger cultural discourses; with a particular focus on how animal training has served as a field for playing out anxieties related to race, class and gender in North America. By applying a Foucauldian genealogical perspective, the book shows how changes in training methods correlate with shifts in dominant regimes of power. It traces the rise and fall of obedience as a category for conceptualizing relationships with dogs.